2014
DOI: 10.1016/j.ccell.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoreceptor TIGIT Regulates Antitumor and Antiviral CD8 + T Cell Effector Function

Abstract: Tumors constitute highly suppressive microenvironments in which infiltrating T cells are "exhausted" by inhibitory receptors such as PD-1. Here we identify TIGIT as a coinhibitory receptor that critically limits antitumor and other CD8(+) T cell-dependent chronic immune responses. TIGIT is highly expressed on human and murine tumor-infiltrating T cells, and, in models of both cancer and chronic viral infection, antibody coblockade of TIGIT and PD-L1 synergistically and specifically enhanced CD8(+) T cell effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
963
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 939 publications
(1,054 citation statements)
references
References 49 publications
38
963
5
1
Order By: Relevance
“…This improvement in therapeutic efficacy following dual blockade of the TIGIT and PD-1 pathways has been demonstrated in the murine colorectal model. 21 In the clinical setting, the survival benefit we observed following delayed anti-TIGIT antibody administration may be promising for achieving disease control for patients with late diagnosis. We also investigated the presence of immunologic memory following treatment by re-challenging long-term survivors with tumor cell injection in the contralateral hemisphere.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This improvement in therapeutic efficacy following dual blockade of the TIGIT and PD-1 pathways has been demonstrated in the murine colorectal model. 21 In the clinical setting, the survival benefit we observed following delayed anti-TIGIT antibody administration may be promising for achieving disease control for patients with late diagnosis. We also investigated the presence of immunologic memory following treatment by re-challenging long-term survivors with tumor cell injection in the contralateral hemisphere.…”
Section: Discussionmentioning
confidence: 92%
“…Likewise, TIGIT expression on TILs has been shown to be upregulated in other solid cancers such as melanoma, colon cancer, and NSCLC in both mice and humans. 19-21 Moreover, it has been suggested that TIGIT expression may indicate dysfunction of CD8 + TILs and reduced effector function. 19 , 20 , 22 These results support the notion of using anti-TIGIT antibody in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dual blockade of 2 immune checkpoints enhance function of tumor infiltrating lymphocytes (TILs) and tumor antigen-specific CD8 þ T cells, thereby, results in significant tumor rejection. 33,34 Lymphocyte activation gene-3 (LAG3) is an immune checkpoint upregulated on activated T cells, T reg , and NK cells. As a homologue to CD4, LAG3 expressed on effector CD4 þ T cells is deemed as a negative modulator tending to have interaction with major histocompatibility complex (MHC) II molecules.…”
Section: Combination Strategiesmentioning
confidence: 99%